2013
DOI: 10.1136/archdischild-2013-304625
|View full text |Cite
|
Sign up to set email alerts
|

Persisting hypoxaemia is an insufficient measure of adverse lung function in very immature infants

Abstract: Background Bronchopulmonary dysplasia (BPD), defined as protracted neonatal hypoxaemia, is considered a risk factor for respiratory disease in adulthood. The relationship between this diagnosis and the actual lung injury appearing in very immature infants is, however, unknown. Objectives To compare lung function at term in very immature infants and full-term infants, and to determine how degree and duration of neonatal hypoxaemia are related to other aspects of lung function. Design and methods All surviving, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
(35 reference statements)
2
13
0
1
Order By: Relevance
“…The findings reported by Hjalmarson et al 2 are in agreement with previous publications that have shown that extreme preterm infants frequently have abnormal lung function later in life, independent of their initial respiratory course compared with infants born at term 3 4. These abnormalities are characterised by lower specific lung compliance and lung volume, combined with airway obstruction that can lead to impaired gas distribution in the distal lung.…”
supporting
confidence: 88%
“…The findings reported by Hjalmarson et al 2 are in agreement with previous publications that have shown that extreme preterm infants frequently have abnormal lung function later in life, independent of their initial respiratory course compared with infants born at term 3 4. These abnormalities are characterised by lower specific lung compliance and lung volume, combined with airway obstruction that can lead to impaired gas distribution in the distal lung.…”
supporting
confidence: 88%
“…Increased Vt is also consistent with results from studies using the multiple-breath washout method. 10 25 However, it contrasts the findings of studies where tidal breathing parameters were assessed with mask-based methods, such as the studies by Schmalisch et al 26 and Hjalmarson and Sandberg. 27 They found that preterm-born infants with chronic lung disease had lower Vt compared with term-born controls, and that a higher V’E was instead related to a substantially higher RR.…”
Section: Discussionmentioning
confidence: 78%
“…To date, the accuracy at predicting respiratory outcomes based on oxygen requirement at 36 weeks is similar to that at 37 weeks, and not substantially improved at 40 weeks 54 supporting the possible dissociation between surrogate measure and clinical disease. Further, it was recently confirmed that lung disease in very preterm infants represents a pathophysiological continuum that may have lasting effects independent of the current 36-week, oxygen-based definitions 55 . This continuum needs to be evaluated in its entirety to provide more precise clinical surrogates of disease severity and to monitor the effect of interventions in improving outcomes.…”
Section: Challenges In Characterization and Prediction Of Bpdmentioning
confidence: 96%